Ectopy on a Single 12‐Lead ECG, Incident Cardiac Myopathy, and Death in the Community. Issue 8 (August 2017) - Nguyen, Kaylin T.; Vittinghoff, Eric; Dewland, Thomas A.; Dukes, Jonathan W.; Soliman, Elsayed Z.; Stein, Phyllis K.; Gottdiener, John S.; Alonso, Alvaro; Chen, Lin Y.; Psaty, Bruce M.; Heckbert, Susan R.; Marcus, Gregory M.
Abstract : Background: Atrial fibrillation and heart failure are 2 of the most common diseases, yet ready means to identify individuals at risk are lacking. The 12‐lead ECG is one of the most accessible tests in medicine. Our objective was to determine whether a premature atrial contraction observed on a standard 12‐lead ECG would predict atrial fibrillation and mortality and whether a premature ventricular contraction would predict heart failure and mortality. Methods and Results: We utilized the CHS (Cardiovascular Health) Study, which followed 5577 participants for a median of 12 years, as the primary cohort. The ARIC (Atherosclerosis Risk in Communities Study), the replication cohort, captured data from 15 792 participants over a median of 22 years. In the CHS, multivariable analyses revealed that a baseline 12‐lead ECG premature atrial contraction predicted a 60% increased risk of atrial fibrillation (hazard ratio, 1.6; 95% CI, 1.3–2.0; P <0.001) and a premature ventricular contraction predicted a 30% increased risk of heart failure (hazard ratio, 1.3; 95% CI, 1.0–1.6; P =0.021). In the negative control analyses, neither predicted incident myocardial infarction. A premature atrial contraction was associated with a 30% increased risk of death (hazard ratio, 1.3; 95% CI, 1.1–1.5; P =0.008) and a premature ventricular contraction was associated with a 20% increased risk of death (hazard ratio, 1.2; 95% CI, 1.0–1.3; P =0.044). Similarly statistically significant results for each analysis were also observed in ARIC. Conclusions: Based on a single standard ECG, a premature atrial contraction predicted incident atrial fibrillation and death and a premature ventricular contraction predicted incident heart failure and death, suggesting that this commonly used test may predict future disease.